2009
DOI: 10.1016/j.cub.2009.10.062
|View full text |Cite
|
Sign up to set email alerts
|

The F-BAR Protein Syp1 Negatively Regulates WASp-Arp2/3 Complex Activity during Endocytic Patch Formation

Abstract: Background Actin polymerization by Arp2/3 complex must be tightly regulated to promote endocytosis. While many Arp2/3 complex activators have been identified, mechanisms for its negative regulation have remained more elusive. We analyzed the yeast arp2-7 allele, which is biochemically unique in causing unregulated actin assembly in vitro in the absence of Arp2/3 activators. Results We examined endocytosis in arp2-7 mutants by live cell imaging of Sla1-GFP, a coat marker, and Abp1-RFP, which marks the later a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 59 publications
5
85
1
Order By: Relevance
“…Las17, the yeast WASp homolog is a major actin nucleation promoting factor (NPF), but it arrives around the time of the late coat factors in wild-type cells and is subject to inhibition by Sla1 and Syp1 during the immobile phase (Boettner et al, 2009;Kaksonen et al, 2003;Rodal et al, 2003;Sun et al, 2006). In the scd5 mutant Las17-GFP had a delay of about +14 seconds, which was fairly similar to that of Sla1 ( Fig.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Las17, the yeast WASp homolog is a major actin nucleation promoting factor (NPF), but it arrives around the time of the late coat factors in wild-type cells and is subject to inhibition by Sla1 and Syp1 during the immobile phase (Boettner et al, 2009;Kaksonen et al, 2003;Rodal et al, 2003;Sun et al, 2006). In the scd5 mutant Las17-GFP had a delay of about +14 seconds, which was fairly similar to that of Sla1 ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Las17 (yeast WASp) arrives at the cortex during the immobile phase of internalization , but its NPF activity is inhibited by Sla1 and Syp1 during this period (Boettner et al, 2012;Boettner et al, 2009;Rodal et al, 2003). We found that overexpression of LAS17 suppressed the ts growth of sla1-DSR at 36˚C and partially rescued the Pan1 lifetimes from ,260 s to ,165 s, P,0.0001.…”
Section: Las17 Overexpression Suppresses Sla1dsrmentioning
confidence: 65%
See 2 more Smart Citations
“…The Syp1 mHD also binds directly to and traffics the transmembrane cargo protein Mid2, which makes Syp1 one the first BAR-domain-containing proteins known to bind cargo. The unstructured middle linker region of Syp1 was also shown to be important in the regulation of actin polymerization through inhibition of Las17 (the yeast ortholog of mammalian WASP) (Boettner et al, 2009).…”
Section: The Muniscin Family Of Endocytic Adaptorsmentioning
confidence: 99%